2011
DOI: 10.2507/22nd.daaam.proceedings.338
|View full text |Cite
|
Sign up to set email alerts
|

Complex Device for Water Analytic

Abstract: Complex photometer described in the paper is a portable device with which it is possible to determine simultaneously both the concentration of certain chemical species in water as well as its electrolytic conductivity. The device can be used for the analysis of independent samples that are found in glass tubes, or of water in displacement through the flow cells using for measurements the flow injection analysis (FIA) (Flow Injection Analysis).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The observation of orthophosphate (PO 4 ) 3− units in alite and belite by replacement of (SiO 4 ) 4− tetrahedra is in agreement with the commonly suggested substitution mechanism from studies of guest ions in pure phases of alite and belite. In cases where phosphorus is considered as the only element of substitution, charge balance may be achieved by creation of Ca 2+ ion vacancies, ,, i.e., 2 false( SiO 4 false) 4 + Ca 2 + 2 false( PO 4 false) 3 + normal◻ Ca These vacancies may explain that only a small amount of phosphate can be incorporated in pure Ca 3 SiO 5 , corresponding to a maximum P/Si ratio of 0.036 . However, in commercial cements a number of other guest ions are incorporated in the calcium silicate phases, Mg, Al, Fe, S, Na, K, and F being the most common elements .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation of orthophosphate (PO 4 ) 3− units in alite and belite by replacement of (SiO 4 ) 4− tetrahedra is in agreement with the commonly suggested substitution mechanism from studies of guest ions in pure phases of alite and belite. In cases where phosphorus is considered as the only element of substitution, charge balance may be achieved by creation of Ca 2+ ion vacancies, ,, i.e., 2 false( SiO 4 false) 4 + Ca 2 + 2 false( PO 4 false) 3 + normal◻ Ca These vacancies may explain that only a small amount of phosphate can be incorporated in pure Ca 3 SiO 5 , corresponding to a maximum P/Si ratio of 0.036 . However, in commercial cements a number of other guest ions are incorporated in the calcium silicate phases, Mg, Al, Fe, S, Na, K, and F being the most common elements .…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies have shown that phosphorus (P 5+ in (PO 4 ) 3− ions) mainly enters the calcium silicate phases with a preferential formation of a phosphatic belite solid solution for phosphorus concentrations above 1 wt % P 2 O 5 . , The upper limit for incorporation of phosphate ions in alite has been reported to be 1.1 wt % P 2 O 5 , corresponding to a molar P/Si ratio of 0.036. Furthermore, incremental addition of P 2 O 5 results in a progressive reduction in the alite content, corresponding to 9.9 wt % per added 1 wt % of P 2 O 5 , which significantly reduces the mechanical strength of the resulting hydrated Portland cement.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of the non-Abelian * -product is reminiscent of the Moyal product in the Weyl quantization approach [48,49] to ordinary nonrelativistic quantum mechanics. Indeed, the study of field theories on noncommutative spacetimes is greatly simplified by the introduction of a Weyl map [50][51][52], which is nothing but the generalization to field theory of the linear map from the classical phase-space functions to functions of quantum operators, first used in Weyl quantization.…”
Section: Noncommutative Spacetimesmentioning
confidence: 99%